2009
DOI: 10.1007/978-1-4419-5692-7_1
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Distributed Respiratory Rhythm Generating Network in the Goldfish (Carsssius auratus)

Abstract: Central pattern generators located in the brainstem regulate ventilatory behaviors in vertebrates. The development of the isolated brainstem preparation has allowed these neural networks to be characterized in a number of aquatic species. The aim of this study was to explore the architecture of the respiratory rhythm-generating site in the goldfish (Carassius auratus) and to determine the utility of a newly developed isolated brainstem preparation, the Sheep Dip. Here we provide evidence for a distributed orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 7 publications
1
16
0
Order By: Relevance
“…Consequently, the pontine area from which the VII nucleus originates also integrates sensory and motor information related to taste, swallowing, and feeding, thus making it possible that the motor output recorded from this nerve reflects nonrespiratory motor behaviors (Milsom et al 2004). While the mean bursting frequency calculated from all our experiments (32 ‫ע‬ 2 bursts min Ϫ1 ) is comparable with previous results obtained in vitro under similar experimental conditions (44.1 ‫ע‬ 7.5 bursts min Ϫ1 ; Duchcherer et al 2010), proper investigation with other approaches (e.g., semi-intact preparations) is necessary to ascertain that the bursting activity recorded is in fact respiratory related. Nevertheless, several lines of evidence give us confidence that this was the case.…”
Section: Critique Of Methodssupporting
confidence: 88%
See 2 more Smart Citations
“…Consequently, the pontine area from which the VII nucleus originates also integrates sensory and motor information related to taste, swallowing, and feeding, thus making it possible that the motor output recorded from this nerve reflects nonrespiratory motor behaviors (Milsom et al 2004). While the mean bursting frequency calculated from all our experiments (32 ‫ע‬ 2 bursts min Ϫ1 ) is comparable with previous results obtained in vitro under similar experimental conditions (44.1 ‫ע‬ 7.5 bursts min Ϫ1 ; Duchcherer et al 2010), proper investigation with other approaches (e.g., semi-intact preparations) is necessary to ascertain that the bursting activity recorded is in fact respiratory related. Nevertheless, several lines of evidence give us confidence that this was the case.…”
Section: Critique Of Methodssupporting
confidence: 88%
“…The brain was irrigated with artificial cerebrospinal fluid (aCSF) at room temperature (20Њ-22ЊC) throughout and after the dissection procedure, which took place in the recording chamber. The composition of the aCSF consisted of (in mM) 120 NaCl, 3.5 KCl, 1.3 MgCl 2 , 11 D-glucose, 13 NaHCO 3 , 1.25 NaH 2 PO 4 , 2.0 CaCl 2 (Duchcherer et al 2010). Tissue Po 2 was not measured in this study.…”
Section: In Vitro Brain Stem Preparationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study using the sheep dip preparation to investigate the rhythm generator responsible for gill ventilation in the teleosts Carssius auratus (a type of carp), we recorded the motor pattern of gill ventilation from the trigeminal nerve while progressively blocking synaptic activity from the caudal to rostral brainstem (Duchcherer et al, 2010). We found that the motor pattern gradually deteriorated as the functional region was reduced.…”
Section: Water Breathing Burst Generatorsmentioning
confidence: 97%
“…The en bloc preparation is amenable for use with a variety of techniques including intracellular recording using sharp microelectrodes, voltage-dependent optical recording of large populations of neurons on the ventral surface and functional transection studies with resolution of 10's of microns that are probably impossible to do in vivo (Duchcherer et al, 2010;Galante et al, 1996a;Oku et al, 2008;Wilson et al, 1999). This preparation generates a close facsimile of the motor pattern recorded in more intact preparations but it has a mildly hypercapnic and acidic core (Torgerson et al, 1997b).…”
Section: Frog Preparations For Studying Control Of Breathingmentioning
confidence: 97%